Riding Free on the Signals of Others - Kim Alexander-Cook; Dan Bernhardt; Joanne Roberts (Queen's University, Department of Economics, 1995)
This paper looks at the incentives to free-ride on the information signaling of others and shows how this can lead to delay in productive activity and to a cascade of activity once information is signaled. In the presence of increasing returns to scale to a profitable project, an initial pioneer may have to incur short-term losses to signal the opportunity to others. Agents may prefer to defer entry in the hope that others will incur those losses and thereby convey the information. Free-riding incentives can be so strong that profitable projects may not be undertaken. Free-riding is worsened when potential entrants must first acquire a costless signal about the project, and this information acquisition is observed: not acquiring the information commits and agent not to incur the entry costs.
Keywords: D82; 330; increasing returns to scale; incomplete information; free-riding; signaling